Situations of work-related diseases and injuries among agriculturists in the upper northeast regions of Thailand [version 3; peer review: 2 approved] - Pornnapa Suggaravetsiri; Sunisa Chaiklieng; Chuthamas Chagkornburee (F1000Research, 2023)
Background: Agriculturists exposed to health hazards are affected by increased occupational disease. This retrospective study aimed to investigate situations of work-related diseases and injuries among agriculturists in upper northeast Thailand. Methods: The secondary data of international classification of diseases 10 th revision (ICD-10) case reports of occupational disease among farmers, from the database of the Health Data Center (HDC), were used. The registered farmers’ data was collected as a dataset from the provincial agricultural office and the data of the ICD-10 code, which was utilized from the hospital information system (HIS) of healthcare services in Udon Thani and Roi-Et provinces, was extracted for cases of work-related diseases and injuries of registered agriculturists. The annual morbidity rate of occupational diseases was analyzed and presented as a rate per 100,000 farmers. Results: Among diseases of farmers in the HDC database, lung disease, which was not reported as an occupational disease of the HDC database, was the highest ranking of all diseases, followed by work-related musculoskeletal disorders (WMSDs), noise- and heat-related diseases, and pesticide toxicity, respectively, while the injury rate was as high as that of WMSDs. Those morbidity rates of Roi-Et and Udon Thani provinces were representative of the morbidity ranking of diseases of the nation and had increasing trends from 2014 to 2016. The number of farmers in the HDC database did not consistently reflect the number of registered farmers in the agricultural database. Conclusions: Situations of work-related diseases and injuries discovered among registered farmers reflect the health problems of Thai agriculturists, and the underestimation in the reported disease rate in the health database is explained by big data analysis, which showed that work-related cases with an identifying code of Y96 had rarely been reported among agriculturists. Therefore, the agriculturists should be supported in registration for occupational diseases and injuries surveillance.